Diagnóstico de la incidencia de los proyectos escolares en el proceso de aprendizaje de educación infantil - Angulo Veliz, Isabel Janeth (2020)
The currently investigation diagnoses the incidence of school projects in students development, due to the self-preparation of the teachers who teach this methodology. For this reason, it is extremely important that educators should be committed and updated in the application of new teaching methods. According to the findings of the observation carried out at the "Patria" Public Education Unit, it was possible to highlight the shortcomings since the subjects were not of interest to the children, the activities were repetitive and not very creative, it is necessary for the teachers to manage strategies that help to develop the skills and competences, focused on the reality and environment of the child, on the other hand it is fundamental the commitment of the authorities of the Institution, providing the necessary support to carry out the constant monitoring of the achievements. In this sense, the purpose of this research is to diagnose the incidence of the problem in the application of school projects and, based on the results, to propose alternatives to improve teaching methods by teachers and thus achieve significant progress in students at the high school level. The research methodology used in this document has both qualitative and quantitative aspects. Qualitative interviews were conducted with teachers and school directors, resulting in a lack of time allocated for the implementation of school projects, Similarly, in the quantitative aspect, we used a relevant instrument such as the survey of parents, and its results correlate with the data obtained in the qualitative form, which clearly show that there is a deficiency in the development of teaching and learning by teachers towards their students. In the same way, in order to corroborate the data, an observation card was implemented, in which the little interest of students, repetitive activities, and the decrease in hours for the development of projects is noted, resulting in coherence in the application of the methods used with their respective tools. This currently work has a research style and the data collected is to use as new recommendations in the area of education and the application of different teaching and learning techniques such as the application of school projects.